The Effect of Basil Leaf (Oscimum sanctum) to the Thrombocytes Number on Mice - Yoni Astuti; Rum Wijayanti (International Journal of Public Health Science (IJPHS), 2016)
Oscimum sanctum is herbal that was spread widely in Indonesia. Oscimum sanctum contains abundant of substances. One of the functions on Oscimum sanctum was anti-thrombocytes effect. This effect is associated with platelet function as a mechanical plug in the vascular injury during the normal homeostatic response. The disruption in thrombocytes function leads to disturb the blood clotting process. Therefore, The aims of the research were to prove the impact of Oscimum sanctum on the number of thrombocytes. This research used mice that divided into 3 groups, as a group I dose 250 mg/day (Oscimum sanctum infusion), group II dose 500 mg/day and the control group. We used clopidogrel as a positive control to determine the effectiveness of anti platelet effect. Data were analyzed by ANOVA showed that the existence of anti-thrombocyte effect in the Oscimum sanctum dose 500 mg/day was significantly different. This result proved that Oscimum sanctum has anti-thrombocytes effect by decreasing thrombocytes number.